Migritude's Decolonial Lessons. Issue 3 (2nd October 2018) - Qadir, Neelofer
ABSTRACT: In this essay, I trace the deep time of the Indian Ocean through and against which Shailja Patel fabulates the notion of migritude and, in particular, what its valences are for solidarities between black and brown Kenyans and other south-south relationships. Attentive to the multiple voices she invites into the text and the material objects that she imbues with those voices, I show how Patel animates histories otherwise obscured toward a larger political project of reckoning with Empire's violences. The essay in three movements meditates on (1) the transmutation of Migritude across generic forms; (2) in the book text, the grafting of Patel's familial history onto (macro) History, which ruptures the telos of modernity by exposing its violences; and (3) the consciousness raising that occurs as Patel accounts for the sexual violence British soldiers perpetrated upon Kenyan women and children from the colonial to the postcolonial period. Migritude 's decolonial lessons move trans-temporally toward the past to repair relationships between women in the Global South, and into our present and its conditional futures to imagine new solidarities and alliances in the heartlands of the dispossessed.